Investigating the Effects of Moral Disengagement and Participation on Unethical Work Behavior - Barsky, Adam (2011)
With massive corruption uncovered in numerous recent corporate scandals, investigating psychological processes underlying unethical behavior among employees has become a critical area of research for organizational scientists. This article seeks to explain why people engage in deceptive and fraudulent activities by focusing on the use of moral-disengagement tactics or rationalizations to justify egregious actions at work. In addition, participation in goal-setting is argued to attenuate the relationship between moral disengagement and unethical behavior. Across two studies, a lab simulation and field survey, a measure of moral disengagement was developed for use with working adults. The hypothesized main and interactive effects of moral disengagement, participation, and unethical behavior were tested and largely confirmed.
Keywords: Self-regulation; Participation; Business Ethics; Moral Disengagement